Structure in 200TI and the odd-even staggering in πh(9/2)*vi(13/2) bands - Kreiner, A. J.; Mariscotti, M. A. J.; Baktash, C.; der Mateosian,E.; Thieberger, P. (1981)
Fil: Kreiner, A. J. Comisión Nacional de Energía Atómica; Argentina